2016
DOI: 10.1088/2043-6262/7/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyol on multiple ligand capped silver alloyed nanobimetallic particles in tri- n -octylphosphine oxide and oleic acid matrices

Abstract: The syntheses of Ag/M (M is Co, Ni, Pd, Pt and Ru) alloyed nanobimetallic particles in tri-n-octylphosphine oxide and oleic acid matrices were successfully carried out by the successive reduction of ligand capped metal ions with polyols, which resulted in rapid precipitation of some fractal high index faceted hybrid Ag/M bimetal nanoparticles. The optical measurements revealed the existence of modified surface plasmon band and peak broadening resulting from reaction-limited growth processes of the metal sols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is generally accepted that crystal structure matching will only take place for two metals whose crystal structures are different in size by less than 5%. 54,65 Metals with small amounts of lattice mismatch can undergo epitaxial growth, where the shell metal will match the crystal lattice and shape of the core metal up to a specific size. 63 Although it is harder to grow highly-mismatched core-shell bimetallic nanoparticles, significant advances have been made toward their synthesis.…”
Section: Bimetallic Nanoparticlesmentioning
confidence: 99%
“…It is generally accepted that crystal structure matching will only take place for two metals whose crystal structures are different in size by less than 5%. 54,65 Metals with small amounts of lattice mismatch can undergo epitaxial growth, where the shell metal will match the crystal lattice and shape of the core metal up to a specific size. 63 Although it is harder to grow highly-mismatched core-shell bimetallic nanoparticles, significant advances have been made toward their synthesis.…”
Section: Bimetallic Nanoparticlesmentioning
confidence: 99%
“…From literature, the crystal structure of AgCoPO 4 had been solved using Patterson and direct method [ 28 ]. So far, preparation of Ag–Co nanoparticles via physical and chemical method was reported [ 29 , 30 , 31 ]; however, few findings were carried out using the plant-influenced green approach. Studies showed that the existence of rare metal is known to enhance the stability of cobalt against oxidation [ 32 ].…”
Section: Introductionmentioning
confidence: 99%